Ezetimibe attenuates functional impairment via inhibition of oxidative stress and inflammation in traumatic spinal cord injury: Ezetimibe attenuates spinal cord injury - Rong, Wei; Li, Huimin; Yang, Huadong; Yuan, Bei; Zhu, Jianjin; Deng, Jiuzheng; Xiao, Songhua; Zhang, Cheng (Cellular and Molecular Biology, 2023)
Sustained inflammation after a traumatic spinal cord injury (TSCI) triggers oxidative stress and neuronal apoptosis, hindering functional recovery. Ezetimibe (EZE) has been reported to have anti-inflammatory and antioxidative properties in hepatology-related diseases, but its potential role in SCI remains unclear. In this study, we evaluated the therapeutic effect of EZE on inflammatory microglia and in an SCI model and elucidated the underlying mechanism. First, we stimulated the BV2 microglia cell line with LPS, and we also induced moderate spinal cord injuries in adult male C57BL/6 mice. Both the cells and mice were treated with EZE, and we investigated inflammation, oxidative stress, neurologic damage, and motor function in vitro and in vivo, respectively. Our findings demonstrated that EZE administration attenuates inflammation in microglia by regulating the AMPK/Nrf2 axis. Furthermore, EZE treatment reduced inflammation and oxidative stress levels in the injured spinal cord. Additionally, treatment with EZE decreased glial scarring and improved motor function recovery, indicating the protective role of EZE in SCI. EZE was found to have anti-inflammatory and antioxidative effects on SCI, and it modulated the AMPK/Nrf2 pathway in microglia. Moreover, EZE prevented histological destruction of the spinal cord tissue. In conclusion, EZE shows promise as a drug to protect neurologic integrity following post-SCI.